Long-term treatment outcomes in children with auditory neuropathy spectrum disorder (ANSD). (May 2020) - Ehrmann-Müller, Désirée; Back, Daniela; Kühn, Heike; Hagen, Rudolf; Shehata-Dieler, Wafaa
Abstract: Introduction: The present article shows long-term results in the hearing and speech development of children with auditory neuropathy spectrum disorder (ANSD). Some children were followed up for nearly 20 years, monitoring their progress through childhood into adulthood. Methods: This retrospective study examined data from 10 children who were diagnosed and treated at our tertiary referral center. All children were provided with hearing aids and/or cochlear implants. The children's hearing and speech development and their social and educational development were evaluated. Results: Seven children were provided with cochlear implants on both sides; three children, one of which had single-sided deafness, received hearing aids. All children with cochlear implants on both sides used their devices full-time. Speech perception ranged between 100% and 0% on one side. Five children attended a school for the hearing impaired; four children attended a regular school. Four children attended vocational training. Conclusions: At present, there is a lack of literature on the long-term outcomes of treatment in children with ANSD. The data presented show that the hearing and speech development in children with ANSD are significantly heterogeneous. Regular school education and social integration of children with ANSD can be achieved with intensive and supportive rehabilitative methods.